2013
DOI: 10.1080/87565641.2012.759580
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Sex Differences Are Not Magnified as a Function of Age, Sex Hormones, or Puberty Development During Early Adolescence

Abstract: Are cognitive sex differences magnified by individual differences in age, sex hormones, or puberty development? Cross-sectional samples of 12- to 14-year-old boys (n = 85) and girls (n = 102) completed tasks assessing episodic memory, face recognition, verbal fluency, and mental rotations. Blood estradiol, free testosterone, and self-rated puberty scores were obtained. Sex differences were found on all cognitive measures. However, the magnitude was not larger for older children, hormones and cognitive performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
2
42
2
Order By: Relevance
“…The apparent developmental pattern of sex differences in cognitive abilities showing consistent findings among adults while inconsistency among children, supports the held view that sex differences in cognition become more common or magnified during adolescence [37]. The underlying mechanism for this pattern involves a complex interplay between biological and environmental variables.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The apparent developmental pattern of sex differences in cognitive abilities showing consistent findings among adults while inconsistency among children, supports the held view that sex differences in cognition become more common or magnified during adolescence [37]. The underlying mechanism for this pattern involves a complex interplay between biological and environmental variables.…”
Section: Introductionsupporting
confidence: 57%
“…This finding is in line with previous studies demonstrating the emergence of sex differences in verbal abilities in childhood. For example, in a cross-sectional study of children aged 12-14, Herlitz et al [37] showed sex differences in verbal fluency without any indication for a larger magnitude during adolescence. Supported by evidence related to sex differences in cortical development [50], their findings joined with the present findings indicate that sex differences in verbal abilities emerge before puberty and imply that the source of these differences should be sought early in development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings of sex-differences in verbal memory in young adults or early adolescents are contradictory. Studies showed no association between the sex-dependent verbal memory and age, level of sex hormone, or puberty development in teenage boys and girls [43]. Furthermore, a recent study including 366 women and 330 men aged between 16 and 69 years of age, showed that women outperformed men on auditory memory tasks due to female advancement in verbal memory, whereas male adolescents and older male adults showed higher level performances on visual episodic and visual working memory measures [44].…”
Section: Sex Differences In Cognitionmentioning
confidence: 99%
“…Studies showed no association between the sex-dependent verbal memory and age, level of sex hormone, or puberty development in teenage boys and girls. 70 Furthermore, a recent study including 366 women and 330 men aged between 16 and 69 years of age, showed that women outperformed men on auditory memory tasks due to female advancement in verbal memory, whereas male adolescents and older male adults showed higher level performances on visual episodic and visual working memory measures. 71 …”
Section: Typical Female-favored Memorymentioning
confidence: 99%